A Relative Analysis of Gardens of Pakistan and UK - Sabir, Talha; Ashraf, Saira; Younis, Muhammad Waqar; Shahzadi, Huma; Rehman, Abdul (Jurnal Locus Penelitian dan Pengabdian, 2024)
Parks play an important role in improving people's quality of life, especially amidst rapid urbanization. This research aims to explore how differences in park design and management affect people's use and perceptions in both countries. The approaches used in this research are qualitative and quantitative. Data were collected through literature review, field observations, and interviews with relevant parties, such as park managers and visitors. The findings show that parks in Pakistan have great cultural significance, often used for social gatherings and recreation, with examples of historical parks such as Shalimar. On the other hand, gardens in the UK offer a diverse range of styles and functions, from formal gardens to natural landscapes, serving as an educational resource for botanical lovers. This analysis provides insights into the unique characteristics of parks in both countries and provides recommendations for park planning and management in Pakistan, taking into account best practices from the UK.